Congenital and perinatal cytomegalovirus infection - Chun Soo Kim (Korean Pediatric Society, 2010)
Cytomegalovirus (CMV) is currently the most common agent of congenital infection and the leading infectious cause of brain damage and hearing loss in children. Symptomatic congenital CMV infections usually result from maternal primary infection during early pregnancy. One half of symptomatic infants have cytomegalic inclusion disease (CID), which is characterized by involvement of multiple organs, in particular, the reticuloendothelial and central nervous system (CNS). Moreover, such involvement may or may not include ocular and auditory damage. Approximately 90% of infants with congenital infection are asymptomatic at birth. Preterm infants with perinatal CMV infection can have symptomatic diseases such as pneumonia, hepatitis, and thrombocytopenia. Microcephaly and abnormal neuroradiologic imaging are associated with a poor prognosis. Hearing loss may occur in both symptomatic and asymptomatic infants with congenital infection and may progress through childhood. Congenital infection is defined by the isolation of CMV from infants within the first 3 weeks of life. Ganciclovir therapy can be considered for infants with symptomatic congenital CMV infection involving the CNS. Pregnant women of seronegative state should be counseled on the importance of good hand washing and other control measures to prevent CMV infection. Heat treatment of infected breast milk at 72?#608;for 5 seconds can eliminate CMV completely.